The world of chaos - Bolotin, Yu.L .; Yanovsky, V.V. (Вопросы атомной науки и техники, 2007)
The present paper is devoted to discussion of origins of the modern paradigm of deterministic chaos: the transition from the older philosophy understanding chaos as a result of uncontrolled external effects to the theory based on internal mechanism of the chaos appearance in nonlinear systems. The report briefly presents the main steps of research in framework of new approach. Success of the new approach is demonstrated on two important dynamical systems – billiards and atomic nuclei.